The effects of adenine nucleotides on cutaneous afferent nerve activity. - Bleehen, T (1978)
1 The activity produced by the adenine nucleotides adenosine triphosphate (ATP), adenosine diphosphate (ADP) and adenosine monophosphate (AMP) and by potassium, acetylcholine (ACh), 5-hydroxytryptamine (5-HT) and bradykinin when applied to an exposed blister base on the ear of anaesthetized rabbits or intra-arterially to anaesthetized cats was investigated in multiple strands dissected from the auricular-temporal and saphenous nerves of rabbits and cats, respectively. 2 In the rabbit preparation potassium and the adenine nucleotides produced activity in the nerve fibres. The effects of these substances were produced in comparable dose ranges; threshold effects being produced by potassium at a concentration of 13 mM and by ADP at a concentration of 4 mM. ACh, 5-HT and bradykinin were inactive at similar or higher concentrations. 3 In the cat preparation all the substances tested produced activity in the nerve fibres. The adenine nucleotides were comparatively less potent than ACh, 5-HT or bradykinin, but had greater potency than potassium. 4 It was concluded that the adenine nucleotides do possess effects on afferent nerve terminals or fibres and thus resemble other known algogenic substances such as potassium, ACh, 5-HT and bradykinin.